Kehamilan Resiko Tinggi pada Ibu Primitua Sekunder Usia 38 Tahun: A Case Report - Dhita Amalya Reivanda; Nuryani Nuryani; Tutiek Herlina; Teta Puji Rahayu (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
High-risk pregnancy is a pregnancy with one or more risk factors that may increase maternal and fetal complications. One of the major risk factors is maternal age ≥35 years with a pregnancy interval of more than 10 years (secondary primiparity). This case report aimed to describe comprehensive midwifery care for Mrs. W, a 38-year-old G3P2A0 woman with a high-risk pregnancy at PMB Bidan "J", Lembeyan, Magetan. This study employed a case report approach using midwifery management with SOAP documentation. The Poedji Rochjati Score Card (KSPR) assessment showed a score of 10, indicating a high-risk pregnancy. Midwifery care included regular antenatal monitoring, education on pregnancy danger signs, implementation of the Birth Planning and Complication Prevention Program (P4K), and postpartum family planning counseling. Throughout the period of care, both maternal and fetal conditions remained stable without complications. Comprehensive midwifery care accompanied by early risk detection using the KSPR contributed to maintaining favorable maternal and fetal outcomes in this high-risk pregnancy.